Clostridium difficile infection in solid organ transplant recipients. Issue 4 (August 2017) - Nanayakkara, Deepa; Nanda, Neha
Abstract : Purpose of review: Clostridium difficile infection (CDI) is a major healthcare-associated infection that causes significant morbidity and an economic impact in the United States. In this review, we provide an overview of Clostridium difficile infection in solid organ transplant recipients with an emphasis on recent literature. Recent findings: C. difficile in solid organ transplant population has unique risk factors. Fecal microbiota transplantation has shown favorable results in treatment of recurrent C. difficile in this population. Preliminary data from animal studies suggests excellent efficacy with immunization against C. difficile toxins. Summary: Over the last decade, number of individuals receiving solid organ transplants has increased exponentially making peri-transplant complications a common occurrence. C. difficile is a frequent cause of morbidity in solid organ transplant recipients. Early and accurate diagnosis of C. difficile requires a stepwise approach. Differentiating between asymptomatic carriage and infection is a diagnostic challenge. Microbial diversity is inversely proportional to risk of C. difficile infection. Antimicrobial stewardship programs help to retain microbial diversity in individuals susceptible to CDI. Recurrent or relapsing C. difficile infection require fecal microbiota transplantation for definitive cure.